Ambrosia beetle’s (COLEOPTERA: CURCULIONIDAE) occurrence and diversity in forest plantations in western Sarawak, Malaysia - Erica Medina Abdullah,; Siti Nurlydia Sazali,; Wan Nurainie Wan Ismail, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Ambrosia beetles (Coleoptera: Curculionidae) are wood-boring beetles that play an important role in temperate forests. They live symbiotically with microorganisms such as fungi that can cause plant wilt and death. In Sarawak, Malaysia, the ambrosia beetles have been found attacking exotic tree species such as Acacia mangium, Acacia crassicarpa and Eucalyptus pellita in some forest plantations. This research aimed to investigate the occurrence of the ambrosia beetles and determined their diversity in forest plantations located in western Sarawak, Malaysia. This research was conducted in exotic plantations at Licence Planted Forest 42 (LPF42), Sampadi, Lundu, and Sabal Model Forest, Simunjan from January 2022 until October 2022. A total of 20 units of modified intercept panel traps baited with 70% ethanol were used in each study site to trap the adult ambrosia beetles. The occurrence and diversity of ambrosia beetles were later analysed using Palentological Statistics Software (PAST). As a result, a total of 170 ambrosia beetles representing 12 species of Scolytinae and two species of Platypodinae were collected. There are seven species comprising 129 individuals of ambrosia beetles collected at LPF42 and 11 species comprising 41 individuals at Sabal Model Forest, respectively. The Shannon-Wiener and Simpson’s indices showed the greatest values in Sabal Model Forest (1.45 and 0.58 respectively), meanwhile, in LPF42 (0.50; 0.28) indicated a range of low to medium species diversity but low species evenness in both study sites. In general, Xylosandrus crassiusculus was dominant in both sites with a total capture of 141 individuals (82.94%). Overall, this study provided baseline information on ambrosia beetle occurrence and their diversity in forest plantations in western Sarawak.